Analysis of the external signals driving the transcriptional regulation of the main genes involved in denitrification in Haloferax mediterranei - Miralles-Robledillo, Jose María; Martínez-Espinosa, Rosa María; Pire, Carmen (Frontiers in Microbiology, 2023)
Haloferax mediterranei is the model microorganism for the study of the nitrogen cycle in haloarchaea. This archaeon cannot only assimilate N-species such as nitrate, nitrite, or ammonia, but it can also perform denitrification under low oxygen conditions, using nitrate or nitrite as alternative electron acceptors. However, the information currently available on the regulation of this alternative respiration in this kind of microorganism is scarce. Therefore, in this research, the study of haloarchaeal denitrification using H. mediterranei has been addressed by analyzing the promoter regions of the four main genes of denitrification (narGH, nirK, nor, and nosZ) through bioinformatics, reporter gene assays under oxic and anoxic conditions and by site-directed mutagenesis of the promoter regions. The results have shown that these four promoter regions share a common semi-palindromic motif that plays a role in the control of the expression levels of nor and nosZ (and probably nirK) genes. Regarding the regulation of the genes under study, it has been concluded that nirK, nor, and nosZ genes share some expression patterns, and therefore their transcription could be under the control of the same regulator whereas nar operon expression displays differences, such as the activation by dimethyl sulfoxide with respect to the expression in the absence of an electron acceptor, which is almost null under anoxic conditions. Finally, the study with different electron acceptors demonstrated that this haloarchaea does not need complete anoxia to perform denitrification. Oxygen concentrations around 100 µM trigger the activation of the four promoters. However, a low oxygen concentration per se is not a strong signal to activate the promoters of the main genes involved in this pathway; high activation also requires the presence of nitrate or nitrite as final electron acceptors